High Performance Reluctance Synchronous Motor Drive using Field Oriented Control - K. Shalini, D. Narmitha, M. Pallavi (Mathematical Statistician and Engineering Applications, 2022)
The ability to improve the performance of Reluctance Synchronous Motors (RSM) using Field Oriented Control (FOC) method. For this purpose, the three-phase RSM is modelled in a rotor (d-q) reference frame. The FOC approach is then created and used to the machine model for a Reluctance Synchronous Motor in a rotor flux-attached spinning (d-q) reference frame. The results reveal that Field Oriented Control is a strong control method for the Reluctance Synchronous Motor, providing improved performance and quicker torque transients (i.,e. less torque settling time). Field Oriented Control has also demonstrated the capacity to increase motor stability and maintain synchronism under heavy loading circumstances.